Safety of prehospital intravenous bolus dose nitroglycerin in patients with acute pulmonary edema: A 4‐year review - Casey Patrick; Louis Fornage; Brad Ward; Michael Wells; Kevin Crocker; Kelly Rogers Keene; Sara Andrabi; Robert Dickson (Journal of the American College of Emergency Physicians Open)
Abstract Background Intravenous nitrates are a primary therapy for hypertensive congestive heart failure (CHF) with acute pulmonary edema (APE) in the hospital setting. Historically, sublingual nitrates are the mainstay of emergency medical services (EMS) pharmacologic therapy for these patients. We aimed to evaluate the safety of prehospital bolus dose intravenous nitroglycerin in patients with APE. Methods This is a retrospective evaluation of EMS data between March 15, 2018, and March 15, 2022, where CHF with APE was suspected and bolus‐dose intravenous nitroglycerin was administered. Protocol inclusion criteria were hypertension (systolic blood pressure [SBP] >160 mmHg) and acute respiratory distress, with a presumption of decompensated CHF with APE. These patients received 1 mg intravenous nitroglycerin, with the option to repeat once for ongoing distress if the SBP remained >160 mmHg. The primary outcomes were adverse events, defined as hypotension (SBP <90 mmHg), syncope, vomiting, or dysrhythmia. Results The final analysis included 235 patients. In patients receiving intravenous bolus nitroglycerin, the median (interquartile range [IQR]) initial and final EMS SBP values decreased from 198 mmHg (180–218) to 168 (148–187), respectively. The median (IQR) pulse decreased from 108 (92–125) to 103 (86–119), and the median oxygen saturation increased from 89% (82–95) to 98% (96–99). Three episodes (1.3%) of asymptomatic hypotension occurred, and none required intervention. Conclusion This study supports a favorable safety profile for prehospital bolus‐dose intravenous nitroglycerin for decompensated CHF with APE. Blood pressure, heart rate, and oxygen saturation improvements are also demonstrated. Further, prospective studies are needed to confirm these findings.